2021
DOI: 10.11648/j.dmath.20210602.11
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of Varicella Zoster Virus Model

Abstract: Chicken Pox (also called Varicella) is a disease caused by a virus known as Varicella Zoster Virus (VZV) also known as human herpes virus 3 (HHV -3). Varicella Zoster Virus (VZV) is a DNA virus of the Herpes group, transmitted by direct contact with infective individuals. In this work, a deterministic mathematical model for transmission dynamics of Varicella Zoster Virus (VZV) with vaccination strategy was solved, using Adomian Decomposition Method (ADM) and Fourth-Fifth Rungekutta Felhberg Method and Approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This model takes into account processes such as power law, fading memory, and crossovers. Note that this article uses a significantly different numerical approach and analysis than [13], which describes the integer ordering problem. It has been shown that the two-scale fractal dimension has a significant impact on the dynamics of the system.…”
Section: Contribution and Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…This model takes into account processes such as power law, fading memory, and crossovers. Note that this article uses a significantly different numerical approach and analysis than [13], which describes the integer ordering problem. It has been shown that the two-scale fractal dimension has a significant impact on the dynamics of the system.…”
Section: Contribution and Noveltymentioning
confidence: 99%
“…These models are known as SIRS models. Following the same assumptions, the model 2 can be written in the following form [13].…”
Section: Introductionmentioning
confidence: 99%